Besarnya Kontribusi Cabe Besar (Capsicum Annum L) Terhadap Pendapatan Petani Padi (Oryza Sativa L) Di Kelurahan Binuang - Bahrun Bahrun (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2013)
ABSTRACTTo the effect research is subject to be know management / chili farming management outgrows and rice, and knows farming income contribution chili outgrow to wetland rice income rain tank at Binuang's sub-district. Contribution or contribution of chili farming outgrows to rice farming income constitute compare of chili farmer earnings outgrows with full scale earnings from farming chili outgrows and RICE farming that is taken into account up to once season plants out. Full scale earnings average as big as Rp. 46. 385. 360,52 / farmers. Contribution on usahatani chili as big as 82,22% and as big as rice farming 17,78% Contribution that gave by chili farming outgrows to sizable rice farmer income which is (82,22%),